Effects of water and phosphorus regulation on photosynthesis and yield of alfalfa in the Yinda Irrigation District - MA Guangyuan; HU Aiping; CHEN Hucheng; ZHANG Rui; LI Yanjun; ZHANG Zhenrong; LI Ping (Guan'gai paishui xuebao, 2025)
【Objective】 Improving water and nutrient use efficiency is essential for promoting sustainable agriculture. This study investigates the combined effects of water and phosphorus applications on growth, photosynthetic characteristics, and yield of alfalfa. 【Method】The experiment was conducted in the Yinda Irrigation District of Gansu Province using the variety Jieyi alfalfa as the model plant. The experiment consisted of three water treatments with soil moisture content kept at 45%-60% (low, W1), 60%-75% (medium, W2), and 75%-90% (high, W3) of the field capacity. For each soil moisture treatment, there were three phosphorus treatments by applying 0 (low, P0), 50 kg/hm2 (medium, P1) and 100 kg/hm2 (high, P2) of phosphorus fertilizer. In each treatment, we measured plant traits, photosynthesis, and hay yield. 【Result】① Under low and medium soil moisture conditions, plant height, stem diameter, leaf-to-stem ratio, photosynthetic performance, and irrigation water use efficiency all increased with phosphorus application, peaking when phosphorous application was 100 kg/hm2. ② Under high soil moisture conditions, these parameters increased initially and then declined with increasing phosphorus application, reaching their maximum when phosphorus application was 50 kg/hm2. ③ When phosphorus application was the same, the impact of soil moisture on hay yield followed the order: high＞medium＞low soil moisture. Among all treatments, the highest yield was achieved under W3P1, which, compared with the low water and low phosphorus treatment, increased the hay yield by 11.78%, 9.51%, and 13.63%, respectively. 【Conclusion】Among all treatments, the optimal water and phosphorus application for maximizing alfalfa hay yield was W3P1, where soil moisture was maintained at 75%-90% of the field capacity throughout the growing period by applying 50 kg/hm2 of phosphorus.